Weight Management Practices among Female Undergraduates: a case study of Nnamdi Azikiwe University, Awka. - C.N , Ogbuji; U. L, Umeh (Journal of Home Economics Research, 2024)
This paper is a case report of the weight management practices of female undergraduates in Nnamdi Azikiwe University, Awka. Four objectives with corresponding four research questions guided the study. Population consisted of 10,500 female undergraduates registered for 2012/2013 academic session. Multi-stage sampling procedure was used to select a sample of 330 female undergraduates for the study. A 22-item questionnaire served as instrument for data collection. Percentages were used to analyze data. The results of the study showed that a good number of the students (76%) engage in healthy weight management practices while a few of them (32%) engaged in unhealthy weight management practices. The reasons for their weight management practices included among others to be attractive, to have a slim physique. Following from the findings of the study, it was recommended among others that parents should inculcate good eating habits in their children, especially the females.